Effects of intermittent and continuous oxytocin infusion on outcomes of pregnancy - Pazandeh, F; Aghakhani, S; Dolatian, M; Alavi Majd, H (Advances in Nursing & Midwifery, 2007)
Abstract Background: Induction of the labor is one of challenging therapies in midwifery. Synthetic oxytocin has been used for many years in obstetric practice for the induction and augmentation of labor. Common side effects of oxytocin are overstimulation, fetal distress and emergency Caesarian section. Despite its extensive use, there is no consensus regarding the initial dose, dosage increments and/or the maximal dose. In addition, there is not enough data to know whether induction or argumentation of labor with oxytocin should be continued or stopped after the onset of active labor. Prolonged oxytocin infusion causes desensitization of oxytocin receptors and reduction of oxytocin receptors MRNA. Purpose: This study was accomplished to compare the effects of intermittent and continuous oxytocin infusion on outcome of pregnancy in those referring to hospital in Maraghe in 2006. Methods: 102 pregnant women were randomly selected and divided into two groups of intermittent and continuous oxytocin infusion. The groups were then matched in terms of parity, age, BMI before pregnancy, gestational age, indication of induction and Bishop score for initiation of oxytocin infusion. Induction of labor in the groups was started by oxytocin infusion of 2mu/min (10 IU of oxytocin was dilated in 1000cc of 0.9% normal saline) and the dosage in the continuous group was increased every 15 minutes by 2mu/min until 3 regular contractions at least 45-60 seconds with moderate severity over 10 minutes. Infusion of oxytocin in intermittent group was discontinued when cervical dilation reached to 5-6 cm but, in the continuous group, infusion of oxytocin was continued at the same level until delivery. Data were collected by a questionnaire, observation of vagina and physical examination. Results: No significant difference was found between the groups regarding the quality of contractions in terms of frequency, duration and severity of contractions (p>0/05). The rate of overstimulation in the continuous group was more. The lengths of active phase in intermittent group were less and the rate of fetal distress in continuous group was more. The rate of Cesarean section in continuous group was less than intermittent group. Conclusion: Further studies in this regard are warranted. Key words: Oxytocin, Labor induced, Outcomes of pregnancy.